Implications of DNA damage in chronic lung disease - Zhang, Dingning; Sun, Tong; Bao, Jiahui; Fu, Jianhua (Frontiers in Cell and Developmental Biology, 2024)
DNA plays an indispensable role in ensuring the perpetuation of life and safeguarding the genetic stability of living organisms. The emergence of diseases linked to a wide spectrum of responses to DNA damage has garnered increasing attention within the scientific community. There is growing evidence that patterns of DNA damage response in the lungs are associated with the onset, progression, and treatment of chronic lung diseases such as chronic obstructive pulmonary disease (COPD), asthma, and bronchopulmonary dysplasia (BPD). Currently, some studies have analyzed the mechanisms by which environmental factors induce lung DNA damage. In this article, we summarize inducible factors of lung DNA damage, current indicators, and methods for diagnosing DNA damage in chronic lung diseases and explore repair mechanisms after DNA damage including nonhomologous end-joining and homology-directed repair end joining pathways. Additionally, drug treatments that may reduce DNA damage or promote repair after it occurs in the lungs are briefly described. In general, more accurate assessment of the degree of lung DNA damage caused by various factors is needed to further elucidate the mechanism of lung DNA damage and repair after damage, so as to search for potential therapeutic targets.